2021
DOI: 10.1002/prot.26185
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of model refinement in CASP14

Abstract: We report here an assessment of the model refinement category of the 14th round of Critical Assessment of Structure Prediction (CASP14). As before, predictors submitted up to five ranked refinements, along with associated residue-level error estimates, for targets that had a wide range of starting quality. The ability of groups to accurately rank their submissions and to predict coordinate error varied widely. Overall, only four groups out-performed a "naïve predictor" corresponding to the resubmission of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 37 publications
(66 reference statements)
1
31
0
Order By: Relevance
“…Some consideration of potential future changes can be found elsewhere in this issue. 30,31 In conclusion, we have shown that the reLLG is a useful addition…”
Section: Relevance Of Refinement Category In Caspmentioning
confidence: 65%
See 1 more Smart Citation
“…Some consideration of potential future changes can be found elsewhere in this issue. 30,31 In conclusion, we have shown that the reLLG is a useful addition…”
Section: Relevance Of Refinement Category In Caspmentioning
confidence: 65%
“…Although the best refinement groups were consistently able to improve the server‐generated refinement targets, most refinement methods degrade the AlphaFold2 models, as seen here for MR as well as for other CASP assessment measures. 30 This is in spite of the lack, in the AlphaFold2 algorithm, 10 of the explicit physics‐based knowledge employed by the most successful refinement groups (e.g., Heo et al 31 ). Figure 12 shows that, with one marginal exception (a slight improvement on an AlphaFold2 starting model), the AlphaFold2 model would have scored equal or higher on the reLLG score compared to the best refined model, even including the double‐barrelled targets starting from AlphaFold2 models.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence of the presence of disordered and flexible regions in human EPO was retrieved based on the analysis of the structural propensity of this protein based on the modeling of its three-dimensional (3D) structure by AlphaFold2 [ 80 ], which is currently the most accurate computational methods to predict 3D protein structures from the protein sequence [ 84 ]. The use of this approach allowed visualization of the whole-length protein, including its signal peptide and regions of missing electron density in previously determined X-ray crystal structure of human EPO.…”
Section: Resultsmentioning
confidence: 99%
“…The refinement category assessor, Daniel Rigden, has looked at this for a subset of seven targets, with GDT_TS values ranging from 72 to 93. 6 These are cases where the best models differed from experiment for small regions of the polypeptide chain, and refinement methods were unable to converge to the experimental structure. Of the 105 residues involved, he found 64 to be close to lattice contacts, suggesting the local conformations are determined by the crystal environment (also not provided to the participants).…”
Section: Crystal Lattice Contactsmentioning
confidence: 99%